The Company's Intellectual Capital: Interaction and Value Creation Case of Tunisian Companies - Mhedhbi, Imen (Journal of Asian Business Strategy, 2013)
The gap between the value of the company in the accounting and financial books and its real market value is growing more and more. This difference represents the effect of intellectual capital that arises in the company in various forms. His cleavage in three types is the most widely used: human capital, organizational capital and customer capital. These different forms of intellectual capital are related to one another and to the financial structure of the company. They correspond to the realization of employees' knowledge skills with their effects on the structure of the company and on creating value for it. In addition, the value is not produced by only one component of intellectual capital, but by their interaction. Our study is to determine a synthesis model explaining these relationships. It does not intend to measure intangible capital of the company (financial and accounting approach), but to determine existing relationships within the intangible assets, on the one hand, and the creation of value for the firm of the other side. We agree, therefore, the qualitative approach and strategic management of intellectual capital.